Principal Leadership Practices in Strengthening Teacher Professionalism: Evidence from Primary Schools in Aceh Tamiang, Indonesia - Buchari Buchari; Siraj Siraj; Cut Khairani; Istiarsyah Istiarsyah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study examines how principal leadership practices strengthen teacher professionalism within the Guru Penggerak program in primary schools in Aceh Tamiang, Indonesia. Using a qualitative multi-case study design, data were collected from four schools through interviews, observations, and document analysis, and were analyzed using the Miles and Huberman interactive model. Findings show that principals enact integrated leadership practices strategic, instructional, transformational, and distributed to support teachers’ pedagogical, personal, social, and professional development. Strategic planning aligned professional development with school needs, while organizational structuring positioned Teacher Leaders as facilitators, mentors, and change agents. Instructional and transformational leadership practices, including coaching, supervision, and motivational support, contributed substantially to collaborative professionalism. Despite challenges such as limited infrastructure, teacher resistance, and administrative burdens, principals applied adaptive strategies such as flexible scheduling, simplified administration, and individualized mentoring. The study concludes that effective leadership is essential for cultivating extended professionalism among Teacher Leaders and provides actionable insights for strengthening the implementation of Indonesia’s educational reforms.